Effect of expertise on arm co-ordination in front crawl - Seiffert, L.; Chollet, D. (Expertise in Elite sport. 2nd International Days of Sport Sciences, 12.-15. November 2002, INSEP, Paris (France), 2002)
Introduction: Three models of arm co-ordination were described in front crawl : catch up, opposition and superposition (Chollet et al., 2000). Using the index of co-ordination (IdC), Chollet et al., (2000) quantified the switching from catch up to opposition in relation with enhancement of velocity, expertise, stroke rate, and decrease of stroke length. Lerda et al., (in press) confirmed for lower performers that with expertise and switching from 800m race to 100m race swimmers switched from catch up to opposition or superposition of arms. Using six swim velocities, from 80% to 100% of maximal velocity, Millet et al., (2002) showed that elite triathletes as elite swimmers had similar increase in IdC except that triathletes decrease smoothly IdC at the maximal velocity while swimmers continued to increase it. The triathletes and the swimmers switched from catch to superposition coordination from 95-97% to the maximal velocity.